The Role of BPJPH: SWOT Analysis in Strengthening and Maximizing the Sharia Economic Ecosystem in Indonesia - Arya Arwanda; M. Adnan Azzaki (EKOMAN: Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This article takes a massive look at the role of BPJPH in the scope of sharia economics which will be analyzed using a SWOT (Strength, Weaknesses, Opportunity and Treatment) study. This article also examines the necessity for a Muslim to complete all his needs with halal products. Of course, this cannot be separated from BPJPH's role in contributing to strengthening the market for the sharia economic ecosystem in Indonesia. Through a qualitative descriptive method with a SWOT analysis approach to be able to provide a comprehensive picture of BPJPH's strategic position. Data were collected in the following ways: First, literature study was used to review official documents. Second, document analysis was carried out by studying the BPJPH report. The results of this article's study show that the strategic role of BPJPH has contributed to strengthening the sharia economic ecosystem, this can be seen from internal and external positions, internally seen from strength where BPJPH has a strong legal basis strategy, government support, mandatory halal certification, collaboration, as well as facilitation for MSMEs supported by training and cross-institutional coordination to accelerate halal certification. Then there are weaknesses in the form of limited institutional capacity, low halal literacy, inadequate digital infrastructure, and budget limitations, which hamper halal certification efforts. In terms of external factors, there are opportunities in the form of exploiting the growth of the global halal market, government support, digitalization, halal tourism, and synergy with industrial players and the sharia economy. Then there are threats in the form of global competition, negative perceptions of halal regulations, differences in international standards, issues of poverty, and counterfeiting of halal logos, which demand an overall increase in halal quality and literacy.